2007
DOI: 10.1136/qshc.2006.020883
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia testing in community pharmacies: evaluation of a feasibility pilot in south east London

Abstract: Background and objective: Chlamydia trachomatis infection is a common sexually transmitted infection with serious sequelae. Excellent access to testing, treatment and contact tracing are an essential part of strategies to control it. With traditional sexual health services overstretched, community pharmacies are well placed to provide this service. They have the potential to improve access by offering chlamydia testing and treatment from high street venues with long opening hours. This study evaluated the feas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 13 publications
3
81
2
1
Order By: Relevance
“…Participation was mainly initiated by pharmacists and it took 5.0 min (0. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] to carry out the screening protocol which involved explaining the study, obtaining consent and clarifying queries.…”
Section: Process Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation was mainly initiated by pharmacists and it took 5.0 min (0. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] to carry out the screening protocol which involved explaining the study, obtaining consent and clarifying queries.…”
Section: Process Feedbackmentioning
confidence: 99%
“…Pharmacies are often the first point of entry into the healthcare system for individuals experiencing symptoms of sleep disorders and pharmacists are well placed to observe medication profiles that may be associated with sleep disorders. In the past, there have been a range of successfully implemented screening systems for cardiovascular risk, diabetes, Chlamydia trachomatis but in contrast, there has only been one study examining screening for sleep disorders [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…177,360,364 Additional factors that may be important for effective organisation and delivery of chlamydia screening in general practice were identified in a qualitative study by McNulty et al 176 Chlamydia screening has been found to be feasible in the community pharmacy setting, and the provision of emergency contraception by pharmacies provides an opportunity to provide chlamydia screening kits simultaneously. 365,366 However, there is a lack of evidence comparing the effectiveness of chlamydia screening in community pharmacy with general practice. Nevertheless, the available evidence suggests pharmacists have experienced some challenges similar to those of general practices, such as lack of privacy and the difficulty of raising the subject of chlamydia in consultations.…”
Section: Chlamydia Screening Uptakementioning
confidence: 99%
“…Another important, practical barrier for youth is cost, and healthcare access will be inequitable unless services are free (World Health Organisation 2009). Community pharmacies cannot meet this criterion without funding to subsidise costs to young patients and customers, but there is evidence demonstrating that this may be both feasible and cost effective; for example for services such as chlamydia screening (Baraitser et al 2007). Condoms and ECP are already provided to young people for free in other countries and this is currently being piloted in NZ (Duff 2013).…”
Section: Service Availabilitymentioning
confidence: 99%
“…International evaluations have indicated success in terms of customer satisfaction and positive health outcomes (Anderson and Blenkinsopp 2006). This has led to the development of other pharmacy-delivered sexual health services including chlamydia screening (Baraitser et al 2007), and the Condom Card ('C-Card) scheme whereby young people are supplied condoms discretely and free of charge via pharmacies (Duff 2013).…”
Section: Introductionmentioning
confidence: 99%